Disegno e verità - Purini, Franco (AND Rivista di architetture, città e architetti, 2017)
As is well known, there are several ways of being an architect. One can start with history in its broadest sense, study a problem, in theory, collect and investigate a series of ancient and modern works from which to draw themes.